Attenuation of Aeromonas hydrophila Infection in Carassius auratus by YtnP, a N-acyl Homoserine Lactonase from Bacillus licheniformis T-1 - Mengfan Peng; Wentao Tong; Zhen Zhao; Ling Xiao; Zhaoyue Wang; Xuanming Liu; Xuanhao He; Zengfu Song (MDPI AG, 2021)
In this experiment, the quorum quenching gene ytnP of Bacillus licheniformis T-1 was cloned and expressed, and the effect against infection of Aeromonas hydrophila ATCC 7966 was evaluated in vitro and vivo. The BLAST results revealed a 99% sequence identity between the ytnP gene of T-1 and its homolog in B.subtilis sub sp. BSP1, and the dendroGram showed that the similarity in the YtnP protein in T-1 was 100% in comparison with B.subtilis 3610, which was categorized as the Aidc cluster of the MBL family. The AHL lactonase activity of the purified YtnP was detected as 1.097 ± 0.7 U/mL with C6-HSL as the substrate. Otherwise, purified YtnP protein could significantly inhibit the biofilm formation of A.hydrophila ATCC 7966 with an inhibition rate of 68%. The MIC of thiamphenicol and doxycycline hydrochloride against A. hydrophila reduced from 4 μg/mL and 0.5 μg/mL to 1 μg/mL and 0.125 μg/mL, respectively, in the presence of YtnP. In addition, YtnP significantly inhibited the expression of five virulence factors hem, ahyB, ast, ep, aerA of A. hydrophila ATCC 7966 as well (p < 0.05). The results of inhibition on virulence showed a time-dependence tendency, while the strongest anti-virulence effects were within 4-24 h. In vivo, when the YtnP protein was co-injected intraperitoneally with A. hydrophila ATCC 7966, it attenuated the pathogenicity of A. hydrophila and the accumulated mortality was 27 ± 4.14% at 96 h, which was significantly lower than the average mortality of 78 ± 2.57% of the Carassius auratus injected with 108 CFU/mL of A. hydrophila ATCC 7966 only (p < 0.001). In conclusion, the AHL lactonase in B. licheniformis T-1 was proven to be YtnP protein and could be developed into an agent against infection of A. hydrophila in aquaculture.